2019
DOI: 10.1021/acs.iecr.9b04840
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Polymer Crystallization Kinetics in the Meltblowing Process

Abstract: A novel model of the crystallization process in meltblowing process is proposed and implemented in numerical simulations. The spinline crystallization is studied using numerical solutions of the system of coupled quasi-one-dimensional equations describing the dynamics of multiple polymer jets moving in the surrounding high-speed air. Cooling, crystallization, and solidification accompany three-dimensional motion of polymer jets resulting in their vigorous stretching by the air flux including the aerodynamicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
(106 reference statements)
1
9
0
Order By: Relevance
“…Uyttendaele et al 10 reported the effects of the processing conditions on the degree of PP fiber crystallization by DSC measurements. The reported degree of crystallization was approximately 0.5, which is similar to the results reported by Hegde and Bhat 122 and Ghosal et al 60 In contrast, Xiao 139 reported a crystallization degree of 0.14 for pure PP meltblown fabric. Using polarized optical microscopy, Yin et al 101 reported that fiber birefringence continued to increase when z > 4 cm, indicating that fiber crystallization occurred after the attenuation of most fibers.…”
Section: Fiber Formation Mechanism Experimentssupporting
confidence: 87%
See 1 more Smart Citation
“…Uyttendaele et al 10 reported the effects of the processing conditions on the degree of PP fiber crystallization by DSC measurements. The reported degree of crystallization was approximately 0.5, which is similar to the results reported by Hegde and Bhat 122 and Ghosal et al 60 In contrast, Xiao 139 reported a crystallization degree of 0.14 for pure PP meltblown fabric. Using polarized optical microscopy, Yin et al 101 reported that fiber birefringence continued to increase when z > 4 cm, indicating that fiber crystallization occurred after the attenuation of most fibers.…”
Section: Fiber Formation Mechanism Experimentssupporting
confidence: 87%
“…Recently, this model was extended to multiple orifices, and in simulating fibrous web structures and fiber crystallization in industrial processes. 60 Chung and Kumar 61 provided a detailed study to elucidate the factors for the fiber vibration in an air jet. An initial displacement, which was not included in Entov and Yarin's quasi-one-dimensional model, 59 was added to simulate the vibration of the fiber while maintaining its straight path.…”
Section: Fiber Formation Theoriesmentioning
confidence: 99%
“…These small peaks disappear in the data obtained with the heating rate of 30°C/min due to recrystallization or crystal perfection/thickening during DSC scanning at lower heating rate 25 . Note also that the present group recently developed a novel theory of crystallization during meltblowing an spunbonding processes used for manufacturing of nonwovens relevant in the present work 27,28 …”
Section: Resultsmentioning
confidence: 72%
“…Note that the calculation of λ via Eqs. ( 39)-( 43) is similar in a sense to the calculation of the degree of crystallization in polymer crystallization processes (Yarin, 1992(Yarin, , 1993Ghosal et al, 2019).…”
Section: Hole Growth Process and The Corona Detachment Timementioning
confidence: 67%